INCREASING STUDENTS’ VOCABULARY BY USING WORD CARDS - Christiaan H. Kaloke; Paula Hampp; Paula Rombepajung (KOMPETENSI, 2021)
The purpose of this study was to find out whether the use of Word Cards is able to increase students’ vocabulary. The students at SMP NEGERI 6 KAKAS in academic year 2019/2020 were chosen as the subject of this study, specified to the seventh grade that consisted of 18 students. This research used pre-experimental design with one group pretest and post-test. This study consisted in five meetings. First the researcher gave a pretest next treatment and the last posttest. The technique in collecting data used test as instrument in form of matching item test consisted with 25 numbers. The result of this study found that Word Cards was effective in increasing students’ vocabulary where post-test was higher than pre-test. The mean score pre-test was 8.27 and the mean score of post-test was 14.61. It can be stated that Word Card is considered effective to increase students’ vocabulary.